1987
DOI: 10.1136/oem.44.11.744
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lead exposure and blood pressure.

Abstract: Recent community studies have suggested that low level lead exposure is significantly associated with blood pressure in the general population. This finding is inconsistent with the results of recent occupational studies of lead exposed workers, although the occupational studies contained serious methodological weaknesses. The present study examined the relation between occupational lead exposure and diastolic and systolic blood pressure in randomly selected samples of 270 exposed and 158 non-exposed workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
12
2
Order By: Relevance
“…Ramirez-Cervantes et al [1978] studied 652 lead foundry workers with at least 5 years of exposure and found no differences in systolic and diastolic blood pressure. In another study, Parkinson et al [1987] examined the relationship between occupational exposure to lead and diastolic and systolic blood pressure in 270 exposed and 158 nonexposed individuals. After considering factors such as age, education, smok-ing habit, alcohol ingestion, and physical activity, they concluded that the association between exposure to lead and blood pressure was weak and nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez-Cervantes et al [1978] studied 652 lead foundry workers with at least 5 years of exposure and found no differences in systolic and diastolic blood pressure. In another study, Parkinson et al [1987] examined the relationship between occupational exposure to lead and diastolic and systolic blood pressure in 270 exposed and 158 nonexposed individuals. After considering factors such as age, education, smok-ing habit, alcohol ingestion, and physical activity, they concluded that the association between exposure to lead and blood pressure was weak and nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a link has been found between blood lead in low concentrations and children's intelligence [Baghurst et al, 1992;Ruff et al, 19931. More important in occupational medicine, the concentration of blood lead was related to blood pressure regulation, but the literature on this subject is controversial [Parkinson et al, 1987;Landrigan, 1991;Goyer, 19931.…”
Section: Introductionmentioning
confidence: 99%
“…Among occupationally and environmentally exposed older adults, associations between BP and blood lead concentrations have been observed in some, but not all, investigations [Parkinson et al, 1987;Hertz-Picciotto and Croft, 1993]. The current study is the first to document a strong association between BP and bone lead among young adults who had very low blood lead concentrations at the time of the investigation, but who were exposed to lead as children.…”
Section: Discussionmentioning
confidence: 59%
“…Not all investigations of the relationship between blood lead concentration and BP have produced positive associations, however [Parkinson et al, 1987;Elwood et al, 1988;Grandjean et al, 1989;Staessen et al, 1990;Sokas et al, 1995;Staessen et al, 1996;Wu et al, 1996;Ehrlich et al, 1998;Nordberg et al, 2000], several suggestions are offered to explain the heterogeneity of results observed. First, it is possible that uncontrolled confounding biased the results of some studies.…”
Section: Introductionmentioning
confidence: 86%